Observer-Independent Quantification of Insulin Granule Exocytosis and Pre-Exocytotic Mobility by TIRF Microscopy. (13th November 2013) - Matz, Magnus; Schumacher, Kirstin; Hatlapatka, Kathrin; Lorenz, Dirk; Baumann, Knut; Rustenbeck, Ingo
Abstract: Total internal reflection fluorescence microscopy of fluorescently labeled secretory granules permits monitoring of exocytosis and the preceding granule behavior in one experiment. While observer-dependent evaluation may be sufficient to quantify exocytosis, most of the other information contained in the video files cannot be accessed this way. The present program performs observer-independent detection of exocytosis and tracking of the entire submembrane population of insulin granules. A precondition is the exact localization of the peak of the granule fluorescence. Tracking is based on the peak base radius, peak intensity, and the precrossing itineraries. Robustness of the tracking was shown by simulated tracks of original granule patterns. Mobility in the X – Y dimension is described by the caging diameter which in contrast to the widely used mean square displacement has an inherent time resolution. Observer-independent detection of exocytosis in MIN6 cells labeled with insulin-EGFP is based on the maximal decrease in fluorescence intensity and position of the centroid of the dissipating cloud of released material. Combining the quantification of KCl-induced insulin exocytosis with the analysis of prefusion mobility showed that during the last 3 s pre-exocytotic granules had a smaller caging diameter than control granules and that it increased significantly immediately before fusion.